About the article: Intermittent fasting scheme and reduction of anthropometric measurements, lipid profile, blood pressure and cardiovascular risk: A propósito del artículo: Esquema de ayuno intermitente y reducción de medidas antropométricas, perfil lipídico, presión arterial y riesgo cardiovascular - Guerra Valencia, Jamee (2022)
Dear Editor:We have read with great interest the article "Intermittent fasting scheme and reduction of anthropometric measurements, lipid profile, blood pressure and cardiovascular risk" published by Dr Javier Wong-Gonzáles et al, in number 1, volume 22 of your magazine; where the purpose of the research focuses on the assessment of the efficacy of intermittent fasting as a strategy for the modification of anthropometric parameters and cardiovascular risk variables; We would like to contribute the importance of defining the times of the day in which the periods of food intake and abstinence are framed during intermittent fasting, since the induced metabolic effects are highly dependent on circadian fluctuations.